Symptoms of muscle dysmorphia, body dysmorphic disorder, and eating disorders in a nonclinical population of adult male weightlifters in Australia - Nieuwoudt, J. E.; Zhou, S.; Coutts, R. A.; Booker, R. (The Journal of Strength and Conditioning Research, 2015)
The current study aimed to (a) determine the rates of symptoms of muscle dysmorphia (MD), body dysmorphic disorder (BDD), and eating disorder; (b) determine the relationships among symptoms of MD, BDD, and eating disorders; and (c) provide a comprehensive comparison of symptoms of MD, BDD, and eating disorders in a nonclinical population of adult male weightlifters in Australia. The participants (N = 648, mean age = 29.5 years, SD = 10.1) participated in an online survey, consisting of Muscle Appearance Satisfaction Scale, the Body Dysmorphic Disorder Questionnaire, and the Eating Attitude Test-26. Results indicated that 110 participants (17%) were at risk of having MD, 69 participants (10.6%) were at risk of having BDD, and 219 participants (33.8%) were at risk of having an eating disorder. Furthermore, 36 participants (5.6%) were found at risk of having both MD and BDD, and 60 participants (9.3%) were at risk of having both MD and an eating disorder. Significant correlations and associations were found between symptoms of MD and BDD, and symptoms of MD and eating disorders. Support was provided for the comorbidity of, and symptomatic similarities between, symptoms of MD and BDD, and symptoms of MD and eating disorders. This may reflect a shared pathogenesis between symptoms of MD, BDD, and eating disorders. Strength and conditioning professionals, exercise scientists, athletic trainers, and personal trainers should be aware that adult males who are working out with weights (i.e., free weights or machines) may be at increased risk of having MD, BDD, and eating disorders.